2021
DOI: 10.1093/nar/gkab1043
|View full text |Cite
|
Sign up to set email alerts
|

proChIPdb: a chromatin immunoprecipitation database for prokaryotic organisms

Abstract: The transcriptional regulatory network in prokaryotes controls global gene expression mostly through transcription factors (TFs), which are DNA-binding proteins. Chromatin immunoprecipitation (ChIP) with DNA sequencing methods can identify TF binding sites across the genome, providing a bottom-up, mechanistic understanding of how gene expression is regulated. ChIP provides indispensable evidence toward the goal of acquiring a comprehensive understanding of cellular adaptation and regulation, including conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…S1C and D ). We also analyzed published epitope-tagged H-NS and StpA ChIP-exo data for K-12 ( 57 ) and found that epitope-tagged H-NS and StpA are similarly distributed in K-12 ( Fig. S1E ), consistent with a ChIP-chip study of K-12 ( 29 ).…”
Section: Resultssupporting
confidence: 81%
“…S1C and D ). We also analyzed published epitope-tagged H-NS and StpA ChIP-exo data for K-12 ( 57 ) and found that epitope-tagged H-NS and StpA are similarly distributed in K-12 ( Fig. S1E ), consistent with a ChIP-chip study of K-12 ( 29 ).…”
Section: Resultssupporting
confidence: 81%
“…Similar patterns are also observed in ChIP binding intensities for multiple auto-activated E . coli TFs curated in the prokaryotic ChIP database, proChIPdb [ 27 ]. For individual TFs, binding peak intensities for positively autoregulated promoters are among the highest of all binding regions across the chromosome ( Fig 4B ), suggesting that strong affinities for the auto-activated promoters may be selected for.…”
Section: Resultsmentioning
confidence: 99%
“…Peak intensities from chromatin immunoprecipitation (ChIP) experiments can reflect binding strengths of a TF to various sites. ChIP peak intensities, defined as signal noise ratio (SNR), were obtained for autoregulated TFs from the prokaryotic ChIP database, proChIPdb [ 27 ]. After subtracting the median of logarithmic intensities of all identified peaks, the resulting values (Δlog 10 SNR) were used to assess the relative binding strength of individual TFBSs.…”
Section: Methodsmentioning
confidence: 99%
“…ChIP-seq raw samples and metadata were downloaded systematically from the SRA. The ChIP-exo subcollection was retrieved from the recently published proChIPdb [27]. This subcollection includes datasets tagged in proChIPdb as 'curated' , as well as TF binding information for OxyR, SoxR, SoxS, and UvrY, from [31,32].…”
Section: Data Gatheringmentioning
confidence: 99%
“…Those have been uploaded into EcoCyc and RegulonDB with a clear HT evidence type along with those identified by classic LT methods. In addition to COLOMBOS with expression data [ 25 ], the Transcription Profile of Escherichia coli (TEC) database [ 26 ], released in 2016, offers gSELEX data in E. coli and the PROkaryotic Chromatin ImmunoPrecipitation database (proChIPdb, [ 27 ]), recently released, offers ChIP-seq and ChIP-exo datasets. However, to our knowledge, there is no comprehensive resource facilitating access in a single place to the diverse wealth of data of different types of objects relevant to the regulation of gene expression in E. coli K-12.…”
Section: Introductionmentioning
confidence: 99%